1974
DOI: 10.1159/000130299
|View full text |Cite
|
Sign up to set email alerts
|

Familial X/X translocation:t(X;X)(p22;q13)

Abstract: We have studied a family with an X/X translocation which was found in a 16-year-old daughter and in her 34-year-old mother. The daughter had short stature, secondary amenorrhea, and many Turner’s stigmata. The mother, 5-ft tall, had a few Turner’s stigmata and had developed secondary amenorrhea at age 24. Both peripheral leukocyte and skin fibroblast cultures of the daughter revealed, by conventional karyotype analysis, 46 chromosomes with one C-group chromosome missing and with an extra No. 2-like chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 3 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…There have been reports of several translocations involving two X chromosomes. Six of the reported cases, as indicated by the literature available to us, have demonstrated that the long arm from one X chromosome was translocated onto the short arm of the other (Quichaud et al 1971, van den Berghe et al 1973, Kim et al 1974, Laurent et al 1975, Ishitobi et al 1976, Daly et al 1977. Therman & Patau (1973) assumed that a Barr body condensation center is located on the proximal part of Xq, and that if an X inv(x) abnormal X chromosome has two such centers, a proportion of the Barr bodies should be bipartite.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There have been reports of several translocations involving two X chromosomes. Six of the reported cases, as indicated by the literature available to us, have demonstrated that the long arm from one X chromosome was translocated onto the short arm of the other (Quichaud et al 1971, van den Berghe et al 1973, Kim et al 1974, Laurent et al 1975, Ishitobi et al 1976, Daly et al 1977. Therman & Patau (1973) assumed that a Barr body condensation center is located on the proximal part of Xq, and that if an X inv(x) abnormal X chromosome has two such centers, a proportion of the Barr bodies should be bipartite.…”
Section: Discussionmentioning
confidence: 92%
“…Several female carriers of unbalanced X-X translocations have been recorded in the literature. Most of them were de novo occurrences and only one family study has included a clinically normal carrier mother of the chromosomal mosaicism (Kim et al 1974). Dollman et al (1972) and Kim et al (1974) presented two different mechanisms for the origin of the X-X translocation: 1) breakage and rearrangement between two X chromosomes, or 2) an uneven number of crossings-over in a pericentric inversion loop during the first meiotic division in a preceding generation.…”
mentioning
confidence: 99%
“…In contrast, a review of the 14 cases with similar recombinant X chromosomes was intriguing (Kim et al, 1974;Laurent et al, 1975;Maeda et al, 1979;Sacchi et al, 1980;Buckton et al, 1981;Nielsen et al, 1982;Duckett and Young, 1988;Aller et al, 1995). The phenotypic manifestations in females with these chromosomal rearrangements are variable, regarding psychosomatic development and reproductive ability (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Duplications of X long and short arms resulting from attachment of X chromosomes or chromatids by long or short arms are now confirmed by banding studies (Disteche et al, 1972;van den Berghe et al, 1973b;de la Chapelle and Stenstrand, 1974;Kim et al, 1974;Ruthner and Golob, 1974b;Therman et al, 1974b). Differences in human i(Xq)s or X long-and short-arm duplications have important implications for understanding the mechanism of their formation and for their use in the study of the role of human X chromosomes in determining phenotype (Ferguson-Smith, 1965).…”
mentioning
confidence: 92%